2005
DOI: 10.1080/15476910590965832
|View full text |Cite
|
Sign up to set email alerts
|

The Use ofIn VitroSystems for Evaluating Immunotoxicity: The Report and Recommendations of an ECVAM Workshop

Abstract: This is the report of a workshop organised by the European Centre for the Validation of Alternative Methods (ECVAM). ECVAM's main goal, as defined in 1993 by its Scientific Advisory Committee, is to promote the scientific and regulatory acceptance of alternative methods that are of importance to the biosciences and which replace, reduce or refine the use of laboratory animals. One of the first priorities set by ECVAM was the implementation of procedures that would enable it to become well informed about the st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
35
0
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 52 publications
(37 citation statements)
references
References 183 publications
(196 reference statements)
1
35
0
1
Order By: Relevance
“…The same holds true especially for immunosuppression (Carfi et al, 2007;Galbiati et al, 2010;Gennari et al, 2005;Langezaal et al, 2001;Lankveld et al, 2010) but also for chronic cell injury, increased secretion of trophic hormones, oxidative stress, and reactive oxygen and nitrogen species (ROS and RNS). An assay for CYP450 induction in cryopreserved human hepatocytes also is currently under prevalidation (Abadie-Viollon et al, 2010;Richert et al, 2010).…”
Section: Specific Considerations For Non-genotoxic Carcinogensmentioning
confidence: 95%
“…The same holds true especially for immunosuppression (Carfi et al, 2007;Galbiati et al, 2010;Gennari et al, 2005;Langezaal et al, 2001;Lankveld et al, 2010) but also for chronic cell injury, increased secretion of trophic hormones, oxidative stress, and reactive oxygen and nitrogen species (ROS and RNS). An assay for CYP450 induction in cryopreserved human hepatocytes also is currently under prevalidation (Abadie-Viollon et al, 2010;Richert et al, 2010).…”
Section: Specific Considerations For Non-genotoxic Carcinogensmentioning
confidence: 95%
“…Furthermore, it was established that the in vitro test should be validated against information gained from humans rather than the results from laboratory animal species. We followed this workshop with a more extensive one in 2003 (Gennari et al, 2005). the recommendations made then still stand and those not addressing sensitization are reproduced in table 2.…”
Section: Consideration 2: Do Environmental Chemicals Cause Relevant Imentioning
confidence: 99%
“…the major limitations of in vitro immunotoxicology and future research needs initially identified (Gennari et al, 2005) still stand as, ten year later, progress has been rather limited. limitations and needs are listed in table 3. the test systems under consideration for assessing chemicalinduced immunosuppression have not really changed (tab.…”
Section: Tab 2: General Recommendations From the Ecvam Workhopmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2003 a workshop hosted by ECVAM was held in order to review the state-of-the-art in the field of in vitro immunotoxicology [109]. Based on its recommendations, an ECVAM-sponsored project was undertaken in which several assays to measure immunosuppression in vitro were compared [110].…”
Section: Immunosuppressionmentioning
confidence: 99%